Electromagnetic shielding effectiveness of amorphous metallic spheroidal- and flake-based magnetodielectric composites. (30th August 2021) - Qian, Kun; Li, Qifan; Sokolov, Alexander; Yu, Chengju; Kulik, Piotr; Fitchorova, Ogheneyunume; Chen, Yajie; Chinnasamy, Chins; Harris, Vincent G.
Graphical abstract: Highlights: Amorphous FeSi-based alloy powders with various aspect ratios > 100:1 have been obtained by a planetary ball mill. The electromagnetic wave shielding effectiveness have been improved by almost 3 times by increasing aspect ratios. The mechanisms for shielding effectiveness are analyzed based on electromagnetic energy absorption and reflection. A loading factor of 40 vol.% of the ∼15 μm diameter powders provided the largest ΔWRL = -20 dB of 9.49 GHz (i.e., 6.55-16.04 GHz) at 2mm coating thickness. Abstract: Flexible, lightweight, conductive materials, having both high rf losses and high permeability, are extremely desirable for applications as electromagnetic (EM) shielding. Gas atomized spherical FeSi-based ferromagnetic metallic particles, having a mean diameter of 14.6 μm with a standard deviation of 7.3 μm, were measured to have a room temperature saturation magnetic flux density of 1.49 T with a coercivity of 160 A/m. Ball milling of the amorphous particles led to aspect ratios from 1:1 (spherical) to > 100:1 (flake-like). Flake-like particles, suspended in paraffin, were found to not only increase the surface area of fillers enhancing the polarization mechanism but also increase the complex permeability and complex permittivity, and thus provide broadband shielding effectiveness. A loading factor of 40 vol.% of the ∼15 μm diameter powders provided the largest Δ W RL = -20 dB of 9.49 GHz (i.e., 6.55< f <16.04 GHz) at a coating thickness of 2 mm. Overall, powder composites show a wide absorption potential above 18 GHz for < 1.5 mm thicknesses. The optimized flake-based composites exhibit strong EM wave absorption with an SE of -40 dB and SE<-10 dB of 17.57 GHz at 40 vol.% filler at a thickness of 1.6 mm.